Analsisis Face Validity dan Content Validity Tes Bahasa Inggris: Sebuah Open Lesson dalam Lesson Study for Learning Community - Syafei, Muh (Journal Prakarsa Paedagogia, 2018)
This paper presents Open Lesson activities in a series of Lesson Study for Learning Community (LSLC) activities in the Language Assessment (LA) course that is taught by the author with partners from other lecturers in the same subject. In this open lesson the theme raised is the material "Analysis of Face Validity and Content Validity of English test" with a duration of 100 (one hundred) minutes which is equivalent to 2 (two) Semester Credit units (SKS) in semester V (odd) 2017 academic year / 2018 in the English Education Study Program, Teaching and Education Faculty of Muria Kudus University. In this paper also discussed the importance of lesson study and its steps, the implementation of Lesson Study for Learning Community at UMK especially in the PBI FKIP UMK, namely the open lesson of Language Assessment courses.